Neuroglycome alterations of hippocampus and prefrontal cortex of juvenile rats chronically exposed to glyphosate-based herbicide - Solomon, Joy; Gutierrez-Reyes, Cristian D.; Chávez-Reyes, Jesús; Onigbinde, Sherifdeen; Marichal-Cancino, Bruno A.; López-Lariz, Carlos H.; Beck, Mia; Mechref, Yehia (Frontiers in Neuroscience, 2024)
Introduction Glyphosate-based herbicides (GBHs) have been shown to have significant neurotoxic effects, affecting both the structure and function of the brain, and potentially contributing to the development of neurodegenerative disorders. Despite the known importance of glycosylation in disease progression, the glycome profile of systems exposed to GBH has not been thoroughly investigated. Methods In this study, we conducted a comprehensive glycomic profiling using LC-MS/MS, on the hippocampus and prefrontal cortex (PFC) of juvenile rats exposed to GBH orally, aiming to identify glyco-signature aberrations after herbicide exposure. Results We observed changes in the glycome profile, particularly in fucosylated, high mannose, and sialofucosylated N-glycans, which may be triggered by GBH exposure. Moreover, we found major significant differences in the N-glycan profiles between the GBH-exposed group and the control group when analyzing each gender independently, in contrast to the analysis that included both genders. Notably, gender differences in the behavioral test of object recognition showed a decreased performance in female animals exposed to GBH compared to controls (p < 0.05), while normal behavior was recorded in GBH-exposed male rats (p > 0.05). Conclusion These findings suggest that glycans may play a role in the neurotoxic effect caused by GBH. The result suggests that gender variation may influence the response to GBH exposure, with potential implications for disease progression and specifically the neurotoxic effects of GBHs. Understanding these gender-specific responses could enhance knowledge of the mechanisms underlying GBH-induced toxicity and its impact on brain health. Overall, our study represents the first detailed analysis of N-glycome profiles in the hippocampus and PFC of rats chronically exposed to GBH. The observed alterations in the expression of N-glycan structures suggest a potential neurotoxic effect associated with chronic GBH exposure, highlighting the importance of further research in this area.